Control of the posoperative bleeding in patíents using anticoagulants mouthwash with tranexamic acid. Implicans of the periodontitis - Méndez Visag, Christian (2005)
This study analysed the hemostatic clinical effect of the tranexamic acid mouthwash against the conventional treatment in patients treated with oral anticoagulants. After suspending the anticoagulant medication for three days, ten surgical procedures were carried out in ten patients(control group), and without modifying or altering the . anticoagulant treatment, 20 procedures were carried out using tranexamic acid in 15 palients(case group). In this last group, before suturing the surgical fleld was irrigated with tranexamic acid solution at 5%. After that, patients of case group were instructed to use 10 ml of the mouthwash for two minutes, tour times a day per seven days. The only statisticaly sígnificative difference (p 0,05) between both groups at the beginning of this research, IOas the level of the anlicoagulation. The average of the INR for case and control group was 2,53 and 1,13 respectively. There weren't significalive differences between both groups with the incidence of postoperatory bleeding . The results of this research have shown that tranexamic acid is effective to control the postoperatory bleeding and the periodontal state is more related lo tire events of bleeding rather than the therapeutic anticoagulation level.